Application of the Think Talk Write (TTW) Learning Model to Improve Student Learning Outcomes in Class XII IPS History Learning at SMAN 1 XIII Koto Kampar - Ghaziah, Putri Tri; Ahmal, Ahmal; Al Fiqri, Yanuar (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The results of observations show that student learning outcomes in the History learning process are not yet optimal, so that student learning outcomes are optimal, it needs to be addressed immediately so that History learning objectives can be implemented well through a learning model that is appropriate to the objectives, namely the Think Talk Write (TTW) learning model for class students. XII IPS SMA Negeri XIII Koto Kampar. This research uses Classroom Action Research, namely planning, implementation, observation and reflection. The research instruments used were the Learning Implementation Plan (RPP) as a learning tool and data collection instruments, namely teacher, student and test observation sheets. In analyzing the data obtained from observations of teacher and student activities by calculating the activities carried out by teachers and students. The results of using the Think Talk Write (TTW) learning model have increased every cycle, in cycle I the average student score was 59/13 with the number of students who completed 7 and in cycle II increased with an average of 86.95 with the number of students who completed 21 people